After Nihilism : essays on Contemporary Art. - Dickhoff, Wilfried (Cambridge : Cambridge University Press, 2000)
Anzinger, Siegfried ; Baechler, Donald ; Beuys, Joseph ; Bleckner, Ross ; Broodthaers, Marcel ; Clemente, Francesco ; Condo, George ; Dahn, Walter ; Dokoupil, Jiri Georg ; Fautrier, Jean ; Förg, Gunther ; Herold, Georg ; Hodgkin, Howard ; Kippenberger, Martin ; Marden, Brice ; Oehlen, Albert ; Penck, A.R. ; Richter, Gerhard ; Salle, David ; Schnabel, Julian ; Schulze, Andreas ; Sherman, Cindy ; Taaffe, Philip ; Trockel, Rosemarie ; van Vliet, Don
Engels
boek